KECELAKAAN LALU LINTAS PADA PENGENDARA SEPEDA MOTOR DI KECAMATAN JAMBI SELATAN KOTA JAMBI TAHUN 2021 - Sucy Deanty; Rara Marisdayana; Eko Mirsiyanto (Sekolah Tinggi Pariwisata Mataram, 2022)
Traffic accidents in Indonesia increase every year, in 2018 the number of traffic accidents was 109,215 cases and increased to 116,411 cases in 2019. The number of traffic accidents in South Jambi District in 2020 was 52 cases. To prevent traffic accidents, it is necessary to do a prevention, one of which is by implementing safety in driving. The purpose of this research is to find out the factors related to preventing traffic accidents on motorcycle riders. The study used a cross sectional approach. The study was conducted in Jambi Selatan District, Jambi City in August 2021. The sample of the study was motorcycle riders in Jambi Selatan District as many as 97 people. The sampling technique used accidental sampling technique. The research instrument is a questionnaire. The data were analyzed using the chi square test. As many as 43.3% of respondents have poor traffic accident prevention, 47.4% of respondents have poor knowledge, 41.2% of respondents have bad attitudes and 38.1% of respondents have not been careful. There is a relationship between knowledge (p=0.000), attitude (p=0.002) and age (p-0.021) with the prevention of traffic accidents on motorcycle riders in the southern Jambi District, Jambi City in 2021. Based on the results of the study it can be concluded that the prevention of traffic accidents Traffic on motorcyclists is related to knowledge, attitude, and age.